2005
DOI: 10.1002/ijc.21598
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐10 expression significantly correlates with minor CD8+ T‐cell infiltration and high microvessel density in patients with gastric cancer

Abstract: We aimed to investigate the relationships between interleukin-10 (IL-10) expression and both the clinicopathological findings and prognoses in patients with gastric cancer and to compare IL-10 expression with microvessel (MV) density and CD81 T lymphocyte infiltration to evaluate its effects on angiogenesis and immune responses in gastric cancer. IL-10 expression was determined in gastric cancer patients by reverse transcription-polymerase chain reaction (RT-PCR) or immunohistochemical procedures. Two of 7 nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0
5

Year Published

2007
2007
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 24 publications
1
43
0
5
Order By: Relevance
“…Matsuguchi et al [27] reported that high serum IL-10 levels in patients with hepatocellular carcinoma presumably also resulted from the secretion of IL-10 by tumor cells. Sakamoto et al [28] demonstrated that IL-10 expression was found in 48% of GC tissues by immunohistochemistry. They found that tumor IL-10 expression was strongly correlated with depth of tumor invasion and with lymph node metastasis, and that IL-10 expression was inversely correlated with CD8+ T-lymphocyte infi ltration.…”
Section: Discussionmentioning
confidence: 99%
“…Matsuguchi et al [27] reported that high serum IL-10 levels in patients with hepatocellular carcinoma presumably also resulted from the secretion of IL-10 by tumor cells. Sakamoto et al [28] demonstrated that IL-10 expression was found in 48% of GC tissues by immunohistochemistry. They found that tumor IL-10 expression was strongly correlated with depth of tumor invasion and with lymph node metastasis, and that IL-10 expression was inversely correlated with CD8+ T-lymphocyte infi ltration.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we have shown that both blood and gastric T cells from gastric cancer patients produce high levels of IL-10 after in vitro stimulation [46]. Furthermore, in a recent study it was shown that IL-10 production by gastric cancer cells correlates with dramatically reduced survival [47].…”
Section: Cd4mentioning
confidence: 97%
“…Therefore, Bv8 produced by these cell types may contribute to angiogenesis and might also have additional regulatory roles that remain to be defined. Originally described as a cytokine produced by T helper 2 cells (52), IL-10 has been also implicated in angiogenesis (53,54).…”
Section: Human Cancer Biologymentioning
confidence: 99%